Recent technical developments and clinical research applications of sodium (23Na) MRI - Gast, Lena; Platt, Tanja; Nagel, Armin Michael; Gerhalter, Teresa (Progress in Nuclear Magnetic Resonance Spectroscopy, 2023)
Sodium is an essential ion that plays a central role in many physiological processes including the transmembrane electrochemical gradient and the maintenance of the body's homeostasis. Due to the crucial role of sodium in the human body, the sodium nucleus is a promising candidate for non-invasively assessing (patho-)physiological changes. Almost 10 years ago, Madelin et al. provided a comprehensive review of methods and applications of sodium (23Na) MRI (Madelin et al., 2014) [1]. More recent review articles have focused mainly on specific applications of 23Na MRI. For example, several articles covered 23Na MRI applications for diseases such as osteoarthritis (Zbyn et al., 2016, Zaric et al., 2020) [2,3], multiple sclerosis (Petracca et al., 2016, Huhn et al., 2019) [4,5] and brain tumors (Schepkin, 2016) [6], or for imaging certain organs such as the kidneys (Zollner et al., 2016) [7], the brain (Shah et al., 2016, Thulborn et al., 2018) [8,9], and the heart (Bottomley, 2016) [10]. Other articles have reviewed technical developments such as radiofrequency (RF) coils for 23Na MRI (Wiggins et al., 2016, Bangerter et al., 2016) [11,12], pulse sequences (Konstandin et al., 2014) [13], image reconstruction methods (Chen et al., 2021) [14], and interleaved/simultaneous imaging techniques (Lopez Kolkovsky et al., 2022) [15]. In addition, 23Na MRI topics have been covered in review articles with broader topics such as multinuclear MRI or ultra-high-field MRI (Niesporek et al., 2019, Hu et al., 2019, Ladd et al., 2018) [16–18]. During the past decade, various research groups have continued working on technical improvements to sodium MRI and have investigated its potential to serve as a diagnostic and prognostic tool. Clinical research applications of 23Na MRI have covered a broad spectrum of diseases, mainly focusing on the brain, cartilage, and skeletal muscle (see Fig. 1). In this article, we aim to provide a comprehensive summary of methodological and hardware developments, as well as a review of various clinical research applications of sodium (23Na) MRI in the last decade (i.e., published from the beginning of 2013 to the end of 2022).
CRIS-Team Scopus Importer:2023-06-09
Keywords: Multinuclear MRI; Sodium (; Sodium ions (Na; Tissue sodium concentration (TSC); X-nuclei imaging

Sodium quantification in skeletal muscle: comparison between Cartesian gradient-echo and radial ultra-short echo time 23Na MRI techniques - Gerhalter, Teresa; Schilling, Felix; Zeitouni, Nour; Linz, Peter; Baudin, Pierre Yves; Kannenkeril, Dennis; Kopp, Christoph; Dahlmann, Anke; Schmieder, Roland; Uder, Michael; Nagel, Armin Michael; Gast, Lena (European Radiology Experimental, 2024)
Background: Clinical magnetic resonance imaging (MRI) studies often use Cartesian gradient-echo (GRE) sequences with 2-ms echo times (TEs) to monitor apparent total sodium concentration (aTSC). We compared Cartesian GRE and ultra-short echo time three-dimensional (3D) radial-readout sequences for measuring skeletal muscle aTSC. Methods: We retrospectively evaluated 211 datasets from 112 volunteers aged 62.3 ± 12.1 years (mean ± standard deviation), acquired at 3 T from the lower leg. For 23Na MRI acquisitions, we used a two-dimensional Cartesian GRE sequence and a density-adapted 3D radial readout sequence with cuboid field-of-view (DA-3D-RAD-C). We calibrated the 23Na MR signal using reference tubes either with or without agarose and subsequently performed a relaxation correction. Additionally, we employed a six-echo 1H GRE sequence and a multi-echo spin-echo sequence to calculate proton density fat fraction (PDFF) and water T2. Paired Wilcoxon signed-rank test, Cohen dz for paired samples, and Spearman correlation were used. Results: Relaxation correction effectively reduced the differences in muscle aTSC between the two acquisition and calibration methods (DA-3D-RAD-C using NaCl/agarose references: 20.05 versus 19.14 mM; dz = 0.395; Cartesian GRE using NaCl/agarose references: 19.50 versus 18.82 mM; dz = 0.427). Both aTSC of the DA-3D-RAD-C and Cartesian GRE acquisitions showed a small but significant correlation with PDFF as well as with water T2. Conclusions: Different 23Na MRI acquisition and calibration approaches affect aTSC values. Applying relaxation correction is advised to minimize the impact of sequence parameters on quantification, and considering additional fat correction is advisable for patients with increased fat fractions. Relevance statement: This study highlights relaxation correction’s role in improving sodium MRI accuracy, paving the way for better disease assessment and comparability of measured sodium signal in patients. Key points: • Differences in MRI acquisition methods hamper the comparability of sodium MRI measurements. • Measured sodium values depend on used MRI sequences and calibration method. • Relaxation correction during postprocessing mitigates these discrepancies. • Thus, relaxation correction enhances accuracy of sodium MRI, aiding its clinical use. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-05-31
Keywords: Calibration; Magnetic resonance imaging; Muscle (skeletal); Sodium; Volunteers